Outage probability computation in multi-backscatter systems with multi-modes of operation - Dinh-Thuan Do; Anh-Tu Le (Bulletin of Electrical Engineering and Informatics, 2022)
In this article, we study the outage performance of an ambient multi-backscatter system supported by non-orthogonal multiple access (NOMA) downlink transmission, where legacy users receive information either directly from the base station (BS) or from multiple backscatter devices (BDs) as well. Specifically, we characterize the network connections between the BS and network users into three modes of operation. In the first mode, the BS communicates with the users via the BDs by exploiting NOMA. In the second mode, the BS communicates directly with the users by employing selection combining (SC) beamforming. In the third mode, the users receive signals from both the BS and BDs simultaneously, by using maximal ratio combining (MRC) to combine the BS and BDs links at the users. Consequently, we derive the exact outage expressions of each mode and utilize Monte Carlo simulations to validate the individual exact expressions.